2015
DOI: 10.2146/ajhp140564
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily aminoglycoside dosing: An update on current literature

Abstract: Once-daily aminoglycoside dosing is an effective, well-established method to achieve therapeutic efficacy while limiting the risk of toxicity and simplifying the processes of dosing and monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 49 publications
(97 reference statements)
1
21
0
2
Order By: Relevance
“…Current clinical guidelines suggest high-dose extended-interval administration of aminoglycosides, reconciling toxicity concerns with efficacy (29,38). Theoretically, such fluctuating stress conditions are predicted to promote the evolution of antibiotic tolerance through increased persister cell formation, rather than to select for resistant mutants (39).…”
Section: Resultsmentioning
confidence: 99%
“…Current clinical guidelines suggest high-dose extended-interval administration of aminoglycosides, reconciling toxicity concerns with efficacy (29,38). Theoretically, such fluctuating stress conditions are predicted to promote the evolution of antibiotic tolerance through increased persister cell formation, rather than to select for resistant mutants (39).…”
Section: Resultsmentioning
confidence: 99%
“…However, this uptake is saturable, and studies have shown that less frequent aminoglycoside administration results in less aminoglycoside uptake and less nephrotoxicity (45). Additionally, once daily dosing provides a higher ratio of peak concentration of drug to minimum inhibitory concentration (MIC), which allows for rapid bacterial killing, and, as the serum concentration declines between dosing intervals, the kidney cells can recover, while the postantibiotic effect of aminoglycosides ensures that bacterial killing persists (46). Prolonged directed therapy is generally reserved for specific indications, including infections due to MDR pathogens.…”
Section: Combination Therapy and Dosing Strategiesmentioning
confidence: 99%
“…We acknowledge that a TDM strategy for plazomicin (and all aminoglycosides) that utilizes serial plasma concentrations at exact time points from a patient during a dosing interval will allow one to better characterize the pharmacokinetic drug profile of that individual. However, while this is feasible in research studies, in the clinical setting, where resources and sampling time are limited, the availability of once-daily nomograms such as the Hartford nomogram (which requires a single blood draw) provides convenience, cost saving, and equivalent patient outcomes (6). Of note, this current study utilized CLcr values available from the various study sites enrolled in the EPIC trial, in contrast to the central study laboratory CLcr values.…”
Section: Discussionmentioning
confidence: 99%